Second primary lung cancer following laryngeal cancer: retrospective study of incidence and multivariate analysis of risk factors in 209 patients. Issue 11 (31st October 2019) - Adams, M; Gray, G; Kelly, A; Toner, F; Ullah, R
Abstract: Objective: To analyse the incidence of second primary lung cancer following treatment for laryngeal cancer and to identify risk factors for its development. Method: Retrospective case series. Results: The five-year actuarial incidence of second primary lung cancer was 8 per cent (1.6 per cent per year). This was associated with a very poor median survival of seven months following diagnosis. Supraglottic tumours were associated with an increased risk of second primary lung cancer compared to glottic tumours in both univariate (hazard ratio = 4.32, p = 0.005) and multivariate analyses (hazard ratio = 4.14, p = 0.03). Conclusion: Second primary lung cancer occurs at a rate of 1.6 per cent per year following a diagnosis of laryngeal cancer, and this is associated in a statistically significant manner with supraglottic primary tumour. The recent National Lung Cancer Screening Trial suggests a survival advantage of 20 per cent at five years with annual screening using low-dose computed tomography scanning of the chest in a comparable cohort to ours. These findings have the potential to inform post-treatment surveillance protocols in the future.